Cat scratch disease in a 23-year-old male–Case report - Waseem, Radeyah; Seher, Muskan; Ghazal, Sohiba; Shah, Hussain Haider; Habiba, Ume (Frontiers in Public Health, 2023)
Cat-scratch disease is an infectious disease that usually presents with fever and tender lymphadenopathy. This infectious disease most often results from a scratch or bite of a cat. The course of this disease depends on the patient’s immunity status. CSD sometimes present as a systemic disease and leads to various disease entities. Here, we describe a case of a 23-year-old male exhibiting fever, generalized weakness and neck swelling. He was started on inotropic drug (meropenem) for low blood pressure and antibiotics (Azithromycin) for fever. Venereal disease research laboratory (VDRL) and Human Immunodeficiency Virus (HIV) serology came out negative. Histopathology ruled out tuberculosis, malignancy and confirmed necrotizing/ suppurative granulomatous inflammation. These features favor the diagnosis of CSD.